Impact of Demographics on Multiple Commitments : Empirical Evidence from Indian Public Sector Undertakings - Saha, Shilpi; Pavan Kumar, S. (Prabandhan: Indian Journal of Management, 2016)
Purpose : The purpose of this study was to determine the demographics that impact multiple commitments in Indian businesses. Design/Methodology/Approach : This research was conducted with the responses of 712 managerial employees working in Indian public sector undertakings. Findings : The results indicated that affective commitment is positively impacted by education. Continuance commitment is positively impacted by age, education, and tenure. Normative commitment is positively impacted by education and tenure. Group commitment is positively related to tenure. Job involvement is positively impacted by age and tenure. Implications : These findings are important for managers so that they can help build and improve different types of commitment of employees in organizations. Originality : This study is unique because it is the first of its kind in India to have investigated demographics for multiple commitments.